Hydrolysis Reactions of p-Nitrophenyl Trifluoroacetate and S-Ethyl Trifluorothioacetate - Jack B. Suggs; Joshua J. Melko (Molecules)
The formation of water structures can provide significant benefits in organic reactions, stabilizing charge and lowering activation energies. Hydrolysis reactions will frequently rely on water networks to accomplish these goals. Here, we used computational chemistry and experimental kinetics to investigate a model thioester molecule S-ethyl trifluorothioacetate, and extended work on a previously characterized ester p-nitrophenyl trifluoroacetate. We found that the rate-determining steps in these reactions are heavily influenced by the nature of the leaving group. The hydrolysis of S-ethyl trifluorothioacetate was much slower than p-nitrophenyl trifluoroacetate for this reason. We explored differences in the reaction orders with respect to water and examined details of calculated potential energy surfaces of these hydrolysis reactions, highlighting the roles of solvation effects and transition state structures.